Communicating climate change: The role of nature-based community development program in enhancing stakeholders engagement - Widhagdha Miftah Faridl; Muktiyo Widodo; Kartono Drajat Tri; Padmaningrum Dwiningtyas (BIO Web of Conferences)
Climate change is a global problem that affects not only the elite but also local communities. Climate change has an impact on both urban and rural inhabitants, with droughts and crop failures among the most severe. In Indonesia, specifically in the village of Sungai Pakning, Bengkalis Regency, Riau Province; the Plaju sub-district, Palembang City, South Sumatra Province; and Klayas village, Sorong Regency, Southwest Papua Province. Climate change poses concern such as peatland fires, coastal erosion, rising temperatures, and limited availability to clean water and local food. This study is a case study undertaken in three places, concentrating on climate change communication initiatives carried out through the use of nature-based community development program. Climate change communication is carried out through the empowerment program by adopting a participatory approach, using local evidence as the primary information basis, involving local actors or local figures, conducting capacity-building training, and forming local community networks, all of which are executed through the implementation of nature-based community development program. The result is that by effectively implementing climate crisis communication, community empowerment programs can strengthen stakeholder engagement.